Annual Plan Proposals Rajasthan 1972-73 - Planning Commission (Planning Commission, 1972)
At the time of formation of Rajasthan peculiar Administrative and Socio- economic conditions prevailed in the state. the Constituent part namely 22 princely States and then part based economy which was mainly dependent on the vagaries degrees of efficiency and a uniformly weak agriculture efforts had been made to derive economic benefits from the land under Plough. the water and mineral resource had remained unemployed and practically no incentives for establishment of industrial units were available.
Rajasthan